Association of the hypertriglyceridemic waist phenotype and type 2 diabetes mellitus among adults in China. Issue 5 (7th March 2016) - Ren, Yongcheng; Zhang, Ming; Zhao, Jingzhi; Wang, Chongjian; Luo, Xinping; Zhang, Jiatong; Zhu, Tian; Li, Xi; Yin, Lei; Pang, Chao; Feng, Tianping; Wang, Bingyuan; et al.
Abstract: Aims/Introduction: To clarify the association of the hypertriglyceridemic waist phenotype and type 2 diabetes mellitus among adults in China. Materials and Methods: In the present case–control study, we included 1, 685 patients with type 2 diabetes mellitus and 7, 141 normal glucose‐tolerant controls from the Henan Province of China in 2011. Elevated waist circumference (GW) was defined as ≥90 cm for men and ≥80 cm for women. Hypertriglyceridemia (HT) was defined as >1.7 m mol/L triglycerides (TG) level. The association of hypertriglyceridemic waist phenotype and type 2 diabetes mellitus was investigated by sex, body mass index, physical activity, and family history of diabetes. Results: Cases and controls differed in age, waist circumference (WC), weight, TG level, fasting glucose, body mass index, smoking status, diabetic family history, physical activity and hypertriglyceridemic waist phenotype ( P < 0.05), but not alcohol drinking ( P = 0.63). In the overall sample, as compared with the phenotype of normal TG level and normal WC (NTNW), normal TG level/enlarged WC (NTGW), elevated TG level/normal WC (HTNW) and elevated TG level/enlarged WC (HTGW) were associated with type 2 diabetes mellitus (odds ratio 4.14, 2.42 and 6.23, respectively). Only HTGW was consistently associated with risk of type 2 diabetes mellitus, with or without adjustment. The strongest relationship between HTGW and type 2 diabetes mellitus was for subjects with body mass index <24.0 kg/m 2 (odds ratio 6.54, 95% confidence interval 4.22–10.14) after adjustment for cofounding variables. Conclusion: HTGW was stably and significantly associated with risk of type 2 diabetes mellitus in adult Chinese. Abstract : The analyses were stratified by sex, body mass index, physical activity, and family history of diabetes for a deeper study of the association of hypertriglyceridemic‐waist phenotype andT2DM. Hypertriglyceridemic‐waist was stably and significantly associated with risk of T2DM among adults in China. Hypertriglyceridemic‐waist was closely associated with T2DM for females and subjects with BMI <24 kg/m 2 .